The Bulletin 2020
DOI: 10.32014/2020.2518-1467.11
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of Explants and Reproduction on Nutrient Medium of Donor Material in Vitro Varieties of Callistephus Chinensis (L.) Ness. For Its Further Use in Landscaping

Abstract: The relevance of the research topic. On the recent methods of biotechnology are increasingly used in plant breeding and seed production. Herbaceous plants such as strawberries, potatoes, a vegetable, some medicinal and others are capable of vegetative propagation the traditional methods of culture, successfully introduced in both in vitro and can achieve a high rate of reproduction. Modern plant biotechnology – the sum of the technologies developed in molecular and cell biology of plants – a new stage in the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…The results of this study are obtained with the use of the Edmondson–Paloheimo model (Edmondson, 1968; Paloheimo, 1974). It has been repeatedly shown that the model relies on rather general assumptions and approximates quite well birth rate in zooplankton, especially in cladocerans (e.g., Hairston, 2015; Mooij et al, 2003; Polishchuk, 1986). There are a number of mathematical derivations of the model (the most elegant and general one is due to Voronov, 1991), which all link birth rate to time intervals equal to D , the egg development time, thus implying that an interval of length D is an adequate sampling interval to estimate birth rate (Polishchuk, 1982, 1986).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The results of this study are obtained with the use of the Edmondson–Paloheimo model (Edmondson, 1968; Paloheimo, 1974). It has been repeatedly shown that the model relies on rather general assumptions and approximates quite well birth rate in zooplankton, especially in cladocerans (e.g., Hairston, 2015; Mooij et al, 2003; Polishchuk, 1986). There are a number of mathematical derivations of the model (the most elegant and general one is due to Voronov, 1991), which all link birth rate to time intervals equal to D , the egg development time, thus implying that an interval of length D is an adequate sampling interval to estimate birth rate (Polishchuk, 1982, 1986).…”
Section: Discussionmentioning
confidence: 98%
“…It has been repeatedly shown that the model relies on rather general assumptions and approximates quite well birth rate in zooplankton, especially in cladocerans (e.g., Hairston, 2015; Mooij et al, 2003; Polishchuk, 1986). There are a number of mathematical derivations of the model (the most elegant and general one is due to Voronov, 1991), which all link birth rate to time intervals equal to D , the egg development time, thus implying that an interval of length D is an adequate sampling interval to estimate birth rate (Polishchuk, 1982, 1986). Given that the egg development time at normal summer temperatures is about 3 or 4 days, this is the reason why in this study sampling intervals are chosen to be just that length.…”
Section: Discussionmentioning
confidence: 98%
“…Наприклад, в освітньому секторі його можна використовувати для оцінювання досліджень і моніторингу навчального процесу. Аналізуючи дані, отримані за допомогою ШІ, викладачі можуть удосконалити навчальну програму та навчальні матеріали, щоб краще відповідати потребам студентів і давати їм змогу досягати кращих результатів [2]. ШІ також можна використовувати для розроблення індивідуальних навчальних програм, які враховують потреби та здібності кожного студента.…”
Section: Ethical and Legal Aspects Of Implementation Of Artificial In...unclassified